Promoting The Role Of Human Resources In Circulation Economy in Vietnam - Gam, Dr. Huynh Thi (The journal of contemporary issues in business and government, 2021)
Until now, Vietnam’s economic activities have mainly relied on the traditional approach, which is a linear economy. This is also the main cause leading to the shortage of natural resources and serious environmental pollution. To overcome these problems, countries in the world, including Vietnam, are moving towards a circular economic development in order to solve the challenge between economic growth and environmental protection, “without trade-off” growth. The economy with environmental pollution and degradation. The World Economic Forum (WEF) also broadcast on its website in early 2020 calling “The world is in need of a cyclic economy”. In that economy, high-quality human resources are becoming increasingly urgent. This study focuses on analyzing the current situation of the circulation economy in Vietnam, the human resources in that economy, thereby posing many issues that need to be discussed in order to develop a circular economy in Vietnam today.